Opting Nursing as a Profession among B.Sc. Nursing Students in India: A descriptive survey research - Khumukcham Anupama Devi; Sudhakar Kumar Singh (International Journal of Medical Research and Review, 2022)
Introduction: Nursing as a career is widely accepted to be viewed positively by society because itprovides job security, mobility, and career variety. As this paper demonstrates, the desire to helpand care for others remains the primary reason for choosing nursing in the twenty-first century. Objective: The purpose of this paper is to determine why B.Sc. Nursing students choose nursing asa career and what factors play a role in their choice. Method and Material: Quantitative,descriptive survey research design adopted and by using convenience sampling collected 312respondents all over India. Self-questionnaires were developed in the google form, and circulatedamong B.Sc. Nursing students and information were collected. Result: Female respondents are fourfolds more and around 51% of respondents appeared in NEET exams before joining a nursing career.Another common misconception that plagues the nursing profession is that students choose nursingas a second career after failing to gain admission to medical school. Conclusion: In general, nursesare extremely enthusiastic about their jobs. Although there are numerous reasons why peoplechoose nursing as a profession, one constant is that nurses can make a difference in someone’s life,as evidenced by all of the COVID-19 cases reported from around the world